RELATIONSHIP OF SERUM TESTOSTERONE LEVELS WITH ANTHROPOMETRIC PARAMETERS OF OBESITY IN YOUNG MALES OF SOUTH PUNJAB - Hassan, Hamid; Sanaullah, Oneeb; Ali, Syed Ahtesham; Javed, Tahira; Imran, Muhammad; Zaidi, Mehreen (Pakistan Journal of Physiology, 2018)
Background: Obesity is the epidemic of current century. It deranges the delicate metabolic and endocrine balance essential for well being of an individual. Men are specifically affected by circumferential obesity which reduces their testosterone level and deprives them of its metabolic, immune and anti inflammatory benefits resulting in emergence of glycemic, atherosclerotic and inflammatory disorders. Methods: It was a cross sectional comparative study carried out at Department of Physiology, Post Graduate Medical Institute (PGMI) Lahore in collaboration with medical OPD of Lahore General Hospital. A total of 40 subjects, between 20 to 40 years of age, were categorised into non obese and obese groups and each group consisted of 20 subjects. Serum testosterone levels of subjects were measured through Enzyme Linked Immunosorbent Assay (ELISA). Results: Testosterone levels, represented as median (IQR), for groups A and B were found to be 680 (575.0–78.5) and 412.5 (338.0–542.5) ng/dl respectively. Serum Testosterone levels of obese subjects were significantly lower as compared to non-obese subjects (p=0.003) and they had an inverse correlation with both Waist Hip Ratio (WHR) (p=0.004) and Waist Circumference (WC) (p=0.002) but not with Body Mass Index (BMI) (p=0.058). Conclusion: Circumferentially obese men have lower testosterone levels as compared to age and ethnicity matched non obese men. WHR and WC have an inverse correlation with serum testosterone levels and they are better indicators for predicting testosterone decline in obese men as compared to BMI. Pak J Physiol 2018;14(4):9–13